2021
DOI: 10.1177/15569845211041343
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Discharge After Shorter Hospitalizations: Lessons Learned Through After-Hours Calls with Thoracic Surgical Patients

Abstract: Objective Minimally invasive procedures coupled with enhanced recovery pathways enable faster postoperative recovery and shorter hospitalizations. However, patients may experience unexpected concerns after return home, prompting after-hours calls. We aimed to characterize concerns prompting after-hours calls to improve discharge strategies. Methods A single-institution, retrospective review was conducted of thoracic surgical patients from 11/4/2019 to 6/14/2020. Records were reviewed and elements of patient de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Post-discharge surveillance is an important part of the pathway, as patients may have additional care needs once home [ 108 ]. A survey indicated that the post-discharge telephone checkup was valued most highly out of all ERAS components postoperatively [ 109 ], follow-up calls aided in answering unexpected questions patients had post discharge (despite prior attempts to optimize knowledge) [ 110 ] and relieving the isolation faced by patients ‘left alone with their illness’ [ 111 ]. Active post-discharge surveillance programs are cost-effective, as postoperative issues may be resolved in the outpatient setting thereby reducing readmission or emergency department presentation [ 112 ].…”
Section: Components Of Erpsmentioning
confidence: 99%
“…Post-discharge surveillance is an important part of the pathway, as patients may have additional care needs once home [ 108 ]. A survey indicated that the post-discharge telephone checkup was valued most highly out of all ERAS components postoperatively [ 109 ], follow-up calls aided in answering unexpected questions patients had post discharge (despite prior attempts to optimize knowledge) [ 110 ] and relieving the isolation faced by patients ‘left alone with their illness’ [ 111 ]. Active post-discharge surveillance programs are cost-effective, as postoperative issues may be resolved in the outpatient setting thereby reducing readmission or emergency department presentation [ 112 ].…”
Section: Components Of Erpsmentioning
confidence: 99%
“…We have employed this model using problem-focused postdischarge telephone calls to identify patients who are at higher risk for emergency department visits and readmissions. [2][3][4] In our experience, many issues during the early postoperative period can be managed by nurses over the telephone, whereas more complex issues have been referred either to the clinic or emergency department. The survivorship model described by Keshava and colleagues 1 shows how health care resource utilization can be optimized beyond the immediate postoperative setting.…”
mentioning
confidence: 99%